The Use of Travel Guidebooks by Tourist Visiting Yogyakarta - Putri, Gabriela Intani; Dewi, Ike Janita (UI Scholars Hub, 2021)
This research aims to know to what extend tourist use travel guidebooks for their visit to Yogyakarta, as one of tourism destination in Indonesia. This research was conducted by taking tourist who has been to or during their visit to Yogyakarta. Qualitative interviews with three travel experts precede this research in order to gather the purpose of using travel guidebooks by tourist visiting Yogyakarta. The results are 31 purposes of using travel guidebooks. After conducting factor analysis and reliability tests, seven factors comprising 26 statements were extracted which are: functional needs, forward-looking needs, learning needs, autonomy needs, tension reduction needs, security needs, and objectification needs.